Conformational Dynamics of the Single Lipopolysaccharide O‐Antigen in Solution. Issue 18 (12th August 2016) - Galochkina, Tatiana; Zlenko, Dmitry; Nesterenko, Alexey; Kovalenko, Ilya; Strakhovskaya, Marina; Averyanov, Alexander; Rubin, Andrey
Abstract: The O‐antigen is the most variable and highly immunogenic part of the lipopolysaccharide molecule that covers the surface of Gram‐negative bacteria and makes up the first line of cellular defense. To provide insight into the details of the O‐antigen arrangement on the membrane surface, we simulated its behavior in solution by molecular dynamics. We developed the energetically favorable O‐antigen conformation by analyzing free‐energy distributions for its disaccharide fragments. Starting from this conformation, we simulated the behavior of the O‐antigen chain on long timescales. Depending on the force field and temperature, the single molecule can undergo reversible or irreversible coil‐to‐globule transitions. The mechanism of these transitions is related either to the rotation of the carbohydrate residues around O‐glycosidic bonds or to flips of the pyranose rings. We found that the presence of rhamnose in the O‐antigen chain crucially increases its conformational mobility. Abstract : To coil or not to coil? The long O‐antigen chain from Salmonella typhimurium demonstrates qualitatively different conformational behavior depending on the temperature and the force field used. Novel simulation scenarios such as single O‐antigen chain collapse into a dense globule or reversible coil‐to‐globule transitions cannot be deduced from the previous results for the shorter oligosaccharides.